2020
DOI: 10.1177/0310057x20940330
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Safer Anaesthesia from Education (SAFE) Obstetric Anaesthesia training course in Ethiopia: A mixed methods longitudinal cohort study

Abstract: Summary Reducing maternal mortality remains a global priority, particularly in low- and middle-income countries (LMICs). The Safer Anaesthesia from Education (SAFE) Obstetric Anaesthesia (OB) course is a three-day refresher course for trained anaesthesia providers addressing common causes of maternal mortality in LMICs. This aim of this study was to investigate the impact of SAFE training for a cohort of anaesthesia providers in Ethiopia. We conducted a mixed methods longitudinal cohort study incorporating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Similar results of SAFE courses have been published from two different regions of Ethiopia [ 33 ]. As the SAFE initiative expands, other models of training and are being developed.…”
Section: Effective Training Programs In Lmicsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results of SAFE courses have been published from two different regions of Ethiopia [ 33 ]. As the SAFE initiative expands, other models of training and are being developed.…”
Section: Effective Training Programs In Lmicsupporting
confidence: 84%
“…Since the first course in 2011, 104 SAFE-OB courses have taken place in 40 countries, and nearly 3244 anaesthesia providers and 581 trainers have been trained [ 33 ].…”
Section: Effective Training Programs In Lmicmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of short courses such as SAFE-OB and the sustainability of its impact in these settings have been scrutinised [10]. Previous studies of SAFE courses have demonstrated retention of skills and knowledge and, through qualitative methods, have reported change in practice and impact at a system level [11][12][13][14][15]. However, no study to date has performed Kirkpatrick Level-3 evaluations to assess the degree to which SAFE course participants apply what they have learnt to their daily job [16].…”
Section: Introductionmentioning
confidence: 99%
“…The SAFE courses focus on obstetric and paediatric anaesthesia [12], and are predominantly focused on pre-and intra-operative care. Follow-up from SAFE courses suggests that these improve skills, confidence and the teamwork abilities of participants [13][14][15][16]. More recently a multidisciplinary course on operating room care [17] has been developed by WFSA; the Association of Anaesthetists; Lifebox Foundation; Royal College of Surgeons of England; Association for Peri-operative Practice; and the Royal College of Obstetricians and Gynaecologists.…”
Section: Introductionmentioning
confidence: 99%